Mitos sobre la sexualidad en adolescentes de la Unidad Educativa del Milenio Diez de Noviembre de la Parroquia los Encuentros, del cantón Yanzatza - Chamba Obelencio, Sofía Alexandra (2019)
Myths about sexuality continue to provoke misinformation, fundamentally in teenagers in which false or mistaken beliefs circulate transmitted among them; in the face of this background, parents, health staff, teachers and the social media must offer correct information about sexuality allowing young people to obtain real data, thereby improving their sexual education. It is a cross-sectional descriptive type study, with a quantitative approach and a sample of 316 students. A survey was used as a technique previously validated and implemented in a free and voluntary informed consent. The tabulation was executed using the Microsoft Excel program and the results were represented in tables. In such a way in the results it was determined that a great percentage on myths in the students do not maintain a good sexual education, so much so that 43 % mention that a pregnancy in stage of breastfeeding does not take place, 67 % consider that in the interrupted coitus does not exist the possibility of a pregnancy, 61 % mention that if a vaginal shower exists after a sexual relation does not originate a pregnancy, based on these mentioned indicators they show a lack of knowledge regarding sexuality. This research was considered relevant and of high importance because at the time of evaluating the myths there was a worrying lack of knowledge among the teenage population and therefore education about teen sexuality should be provided. Keywords: Young people, education, indicators.